Microbiological assessment and ph measurement in ground beef available in supermarkets in Southern Bahia: Caracterização microbiológica e pH de carne bovina moída comercializada em supermercados no Sul da Bahia - Deminicis , Renata Gomes Da Silveira; Deminicis, Bruno Borges (Scientia Agraria Paranaensis, 2022)
Assessment of the microbiological quality and pH of foods available in supermarkets is vital to guarantee food safety, offering consumers essential information about the integrity and freshness of products. Therefore, the objective of this study was to evaluate the microbiological quality and pH of the beef most sold in supermarkets in southern Bahia. Forty supermarkets that sell fresh ground beef were randomly selected in four counties in the south of the state of Bahia, Brazil, to collect and prepare “ground beef” samples. 20 simple samples of 100 g of ground meat from non-specific cuts were collected (different cuts in the ground mixture, e.g.: duckling, shoulder, tough leg, chuck, breast or flank steak), as is common in regional trade, collected in each of the establishments. Researched, totaling 800 simple samples. The simple samples were homogenized, constituting a composite sample per establishment, totaling 40 samples, which were then identified and transported to the Laboratory in isothermal boxes, properly refrigerated. Once the samples were in possession, the pH was measured and microbiological analyzes were carried out, using techniques to identify mesophilic aerobic bacteria, molds and yeasts. The most likely number of total coliforms ranges from 21 to 2.7 x 104 MLN g-1 (average 3.5x103 MLN g-1), and coliforms at 45ºC or thermotolerant <3 to 5 x 103 MLN g-1 (average 1.3x103 MLN g-1). The presence of Escherichia coli was confirmed in 70% of the samples. No Salmonella was detected in any of the samples. Most samples were within the standards determined by current legislation, with the absence of Salmonella in 25g of sample. The average PAN of coliforms at 35°C and 45°C complied with national and international legislation, however, the verification of the presence of E. coli in 16 samples (40% occurrence) shows a medium risk of colibacillosis occurrence transmitted by meat. Even so, the risk of transmission of these diseases cannot be rejected, since the presence of E. coli is independent of the number of coliforms and the national legal standards established for the group of thermotolerant coliforms. Regarding the pH, one sample (2.5%) showed characteristics of beginning of decomposition, as it had a pH above 6.4.